(untitled) (Research, Society and Development, 2020)
The authors sought bone alterations in the ribs of 12 bones from the exhumation of corpses from a public cemetery in Cascavel-PR, which were donated to the university for teaching and research purposes. In this examination, the presence of a bone protuberance of 0.7 mm in length and 0.4 mm in thickness was observed in the intrathoracic region of a rib of the right antimere. This finding is compatible with the condition of solitary Exostosis and is present in a rare site of involvement. The presence of this finding can lead to chest pain or discomfort, since the compression caused by this structure is uncomfortable or it can be asymptomatic and of casual diagnosis. In addition, it can lead to severe conditions such as pneumothorax, hemothorax, neural compression and even sarcomatous degeneration. Thus, a professional investigation that may be necessary in order to avoid future complications.